2008
DOI: 10.1111/j.1471-1842.2008.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the information and resource needs of UK health and social care placement students

Abstract: Background : Students on health and social care degree programmes spend 50% of their time on practice placements. Because of the diversity of settings and the need to evidence their work, it is vital to understand the information and resource needs of placement students. Objectives : The aim of this investigation was to understand the needs of placement students in terms of accessing resources whilst they are in the field in order to inform a guide to meet these needs. Methods : Focus groups were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, a figure of 38.1% ( n = 96) responded that they did not know or were not sure and this suggests significant room for improvement. Feedback that ‘not enough attention was given to induction and training to access and use of library‐based and electronic resources’ suggests this remains an issue. Informing students of sources of support before placement, and if possible at the clinical location, would be useful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a figure of 38.1% ( n = 96) responded that they did not know or were not sure and this suggests significant room for improvement. Feedback that ‘not enough attention was given to induction and training to access and use of library‐based and electronic resources’ suggests this remains an issue. Informing students of sources of support before placement, and if possible at the clinical location, would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…This was, as noted by Mailer, because of their previous experience of placements and exposure to both NHS and HE libraries. In order to extend the literature base already in existence on this topic, students from the three departments representing HSC, Nursing and Midwifery, Allied Health and Health and Applied Social Sciences, were approached, which offered a wide based research sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most Barriers Scale items associated with practitioners were not rated as significant barriers, comments showed that some counsellors believed that treatment should stem almost exclusively from experience and evolving client need, rather than from literature-based research. Other studies have found social care cultures to be experiential rather than empirically based (Callaghan et al, 2008;Lewig et al, 2006).…”
Section: Practitionermentioning
confidence: 99%
“…The schedule was guided by existing research (Callaghan, Doherty, Lea, & Webster, 2008), and began with an introduction followed by an opening question (about research information sources) designed to promote thinking around research use. To encourage open dialogue, just two core questions (about experiences of barriers and facilitators) were asked.…”
Section: Focus Groupsmentioning
confidence: 99%